Global research trends on Chinese patent drugs inducing programmed cell death in cancer: a bibliometric analysis (1998–2024) - Min Song; Chunyan Teng; Xiaodong Zheng; Shizhen Tan; Yipeng Guo (Discover Oncology)
Abstract Background Chinese patent drugs, standardized formulations rooted in traditional Chinese medicine, have gained attention for their potential to induce programmed cell death (PCD) in cancer cells. Emerging evidence suggests that these formulations may affect multiple PCD pathways, including apoptosis, autophagy, ferroptosis, pyroptosis, and necroptosis, thus offering a multifaceted approach to tumor suppression. Objectives This study aimed to map the global research landscape on Chinese patent drugs in cancer-related PCD, examining publication trends, principal contributors, and thematic evolutions. The analysis also sought to provide insights that could guide future investigations and clinical applications. Methods Bibliometric data were extracted from the Web of Science Core Collection (1998–2023), focusing on articles investigating Chinese patent drugs and PCD in oncological contexts. R-bibliometrix was used for descriptive statistics and trend analyses, while VOSviewer generated network visualizations of co‐occurring keywords, collaboration patterns, and co‐citation clusters. Results Overall publication output increased markedly, with China leading in both volume and impact. Collaboration networks revealed extensive international partnerships, underscoring global interest in standardized herbal formulations. Keyword mapping highlighted a shift from early apoptosis-centric studies to more diverse regulated cell‐death pathways, indicating greater mechanistic depth and exploration of synergistic effects with conventional therapies. Conclusion Chinese patent drugs are increasingly recognized as promising agents for modulating PCD in cancer cells. Ongoing work focuses on standardized manufacturing, robust clinical validation, and mechanistic elucidation. These trends position Chinese patent drugs at a pivotal juncture for advancing integrative oncology and enhancing patient outcomes.